2008
DOI: 10.2337/db07-1358
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Missense Mutations in the Insulin Gene Are Linked to Permanent Diabetes Appearing in the Neonatal Period or in Early Infancy

Abstract: OBJECTIVE—Permanent neonatal diabetes (PND) is defined by chronic hyperglycemia due to severe nonautoimmune insulin deficiency diagnosed in the first months of life. Several genes, including KCNJ11 and ABCC8, which encode the two subunits of the ATP-sensitive K+ channel (KATP channel) can cause PND. Mutations in the insulin (INS) gene have been recently described in families with neonatal diabetes. Our study aimed to investigate the genetic anomalies and clinical heterogeneity in PND patients who are negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 25 publications
3
90
0
1
Order By: Relevance
“…Moreover, mutations in diverse genes leading to β-cell ER stress contribute to the development of diabetes in humans (Inoue et al 1998, Delepine et al 2000, Stoy et al 2007, Colombo et al 2008, Polak et al 2008. These results suggest that tight control of ER homeostasis is crucial to maintain β-cell function and survival.…”
Section: R4mentioning
confidence: 87%
“…Moreover, mutations in diverse genes leading to β-cell ER stress contribute to the development of diabetes in humans (Inoue et al 1998, Delepine et al 2000, Stoy et al 2007, Colombo et al 2008, Polak et al 2008. These results suggest that tight control of ER homeostasis is crucial to maintain β-cell function and survival.…”
Section: R4mentioning
confidence: 87%
“…Differences in the underlying pathophysiology explain why patients with recessive INS mutations are diagnosed earlier and have a lower birth weight than patients with heterozygous INS mutations (8)(9)(10)(11)(12). The disrupted insulin synthesis seen with recessive mutations occurs as soon as the fetal beta cell starts to secrete insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous missense mutations in the coding region of the INS gene have recently been described as a cause of neonatal diabetes (8)(9)(10)(11)(12). Most of the reported mutations are predicted to disrupt the folding of the proinsulin molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, variation or mutation of the same gene can cause monogenic diabetes but also contribute to individual risk of the very common, polygenic type 2 diabetes (3-7). Recent studies indicated that autosomal dominant insulin gene mutations can cause permanent neonatal diabetes (PND) but also autoantibody-negative diabetes that is classified then as type 1B or maturity-onset diabetes of the young (MODY)-type diabetes (8)(9)(10). The molecular mechanism behind these cases with a MODY-like presentation was suggested to be defective trafficking of proinsulin and increased endoplasmic reticulum (ER) stress (11).…”
Section: Introductionmentioning
confidence: 99%